Fertigated Sugarcane Yield and Carbon Isotope Discrimination (Delta C-13) Related to Nitrogen Nutrition - Kolln, Oriel Tiago; Castro Gava, Glauber Jose de; Cantarella, Heitor; Junqueira Franco, Henrique Coutinho; Martinez Uribe, Raul Andres; Rocha Pannuti, Luiz Eduardo da [UNESP]; Ocheuze Trivelin, Paulo Cesar (Springer, 2016)
The aim of this study was to evaluate the response of sugarcane to nitrogen (N) application with drip irrigation and the relation with carbon isotope discrimination (Delta C-13), aboveground dry matter cane yield and the N balance in consecutive ratoon crops of sugarcane. An experiment was set up in Jau, SP, Brazil, in which the second and third ratoon crop cycles (2008/2009 and 2009/2010) were evaluated. The experiment included an unfertilized N control in both years (T1), and the following three nitrogen (N) fertilizer rates (in kg ha(-1)) applied in 2008 and 2009, respectively: 70 and 50 (T2), 140 and 100 (T3), and 210 and 150 (T4). Fertilization with N caused a marked gain in stalk yields by 98 Mg ha(-1) in 2 years. The N export with harvest was higher than N application in the control treatment T1 and at the lower rate (T2); this, in addition to the observed linear response to N, indicate the need to increase N fertilization in irrigated sugarcane. The values of Delta C-13 decreased with the increase of N supply showing a significant negative correlation (p < 0.05) with stalk as well as whole plant aboveground dry matter yields. The values of Delta C-13 in top leaves may be used as a tool to characterize the N status of sugarcane plants and its relation to aboveground dry matter and yield.
Keywords: Drip-irrigation; C-4 plants; Water management; Sugar; N fertilization